“Literary Critics Make Natural Detectives” - Or Do They? Detection and Interpretation in A. S. Byatt’s Possession: A Romance - Agnieszka Seredyńska (Polish Journal of English Studies, 2022)
This paper explores the themes of detection and interpretation in A. S. Byatt’s Possession. A Romance, which, I argue, are interconnected in two ways. Firstly, the plot centres around an investigation conducted by a pair of academics, who exercise their skills as literary critics to piece together the story of two Victorian poets. Secondly, the novel’s structure, specifically the inclusion of the pseudo-Victorian intertexts the scholars use as evidence, offers the reader an opportunity to become an armchair detective and perform the interpretive work undertaken by the modern-day characters. Even so, this article aims to demonstrate that Possession actively resists this detective-like approach to literature. Byatt’s critics prove blundering sleuths, relying on lucky coincidence and intuitive apprehension more than reasoning and critical insight, and the conclusions they arrive at turn out to be partially misguided. Furthermore, a close-reading of the pseudo-Victorian intertexts challenges the assumption that literature offers an unproblematic window into its author’s life and feelings, which the investigation tacitly relies on. The article contends that despite the writerly games Possession plays with its audience, it ultimately favours a non-academic approach to reading as opposed to one that takes the text apart in search for meaning.